Results of the European survey on the assessment of deep molecular response in chronic phase CML patients during tyrosine kinase inhibitor therapy (EUREKA registry) - Möbius, Susanne; Saußele, Susanne (Journal of cancer research and clinical oncology, 2019)
PurposeThe advent of tyrosine kinase inhibitor (TKI) therapies has revolutionized the treatment of chronic myeloid leukemia (CML). The European LeukemiaNet (ELN) recommends quantification of BCR-ABL1 transcripts by real-time quantitative PCR every 3 months during TKI treatment. Since a proportion of patients in deep molecular response (DMR: MR4, MR4.5, MR5) maintain remission after treatment stop, assessment of DMR is crucial. However, systematically collected molecular data, monitored with sensitive standardized assays, are not available outside clinical trials.MethodsData were collected on the standardized assessment of molecular response in the context of real-life practice. BCR-ABL1 transcript levels after > 2 years of TKI therapy were evaluated for DMR by local laboratories as well as standardized EUTOS laboratories. Since standardized molecular monitoring is a prerequisite for treatment discontinuation, central surveillance of the performance of the participating laboratories was carried out.ResultsBetween 2014 and 2017, 3377 peripheral blood samples from 1117 CML patients were shipped to 11 standardized reference laboratories in six European countries. BCR-ABL1 transcript types were b3a2 (41.63%), b2a2 (29.99%), b2a2/b3a2 (3.58%) and atypical (0.54%). For 23.72% of the patients, the initial transcript type had not been reported. Response levels (EUTOS laboratory) were: no MMR, n = 197 (6.51%); MMR, n = 496 (16.40%); MR4, n = 685 (22.64%); MR4.5, n = 937 (30.98%); MR5, n = 710 (23.47%). With a Cohen’s kappa coefficient of 0.708, a substantial agreement between EUTOS-certified and local laboratories was shown.ConclusionsMulticenter DMR assessment is feasible in the context of real-life clinical practice in Europe. Information on the BCR-ABL1 transcript type at diagnosis is crucial to accurately monitor patients’ molecular response during or after TKI therapy.
Gesehen am 30.10.2019